(untitled) (Research, Society and Development, 2023)
The production of tiquira (cassava spirit) can benefit rural producers and encourage the production chain by resulting in a product with high added value. In this context, the study sought to investigate the organoleptic, physical-chemical and toxicological characterization of tiquira cachaça sold in the ver-o-peso market located in Belém-PA. The samples in the present study were analyzed in the laboratory facilities of the Centro Universitário da Amazônia - UNIESAMAZ. Three samples called A, B and C of tiquira cachaça were used for each analysis. In the organoleptic characterization, C presented a foreign body and B and C presented an improper color. Regarding the other definitions (bloating, leakage, odor and gas), the samples were found to be in accordance with the standards established by MAPA. The results obtained in the physical-chemical analyzes were °Brix 14.86, 13.96 and 14.93, pH of 5.08, 5.15 and 5.44, alcohol content of 41% to 42% at 20°c (%v/v), total acidity of 0.195g/100g, 0.063g/100g and 0.234g/100g, fixed acidity of 0.07g/100g, 0.13g/100g and 0.2g/100g, volatile acidity of 304, 8mg ac. acetic/100ml, 159.5mg/100ml ac. acetic and 80.9mg acetic/100ml, density of 0.5068g/ml, o.9504g/ml and 0.9457g/m and qualitative test for absent proteins. Regarding the toxicological results of methemoglobin in vitro, the results were positive for all samples. The analyzes in this study are important regarding the production of artisanal food and drinks, as there is little supervision regarding the production of drinks sold in open-air markets. As tiquira is an artisanal cachaça produced in stills, it can suffer contamination in the production process, however such analyzes offer an alternative for inspection and evaluation of its chemical characteristics, in addition to having the aim of protecting the public health of consumers.